Lepton flavor violating decays of neutral higgses in extended mirror fermion model - Chia-Feng Chang; Chia-Hung Vincent Chang; Chrisna Setyo Nugroho; Tzu-Chiang Yuan (Nuclear Physics B, 2016)
We investigate the one-loop induced charged lepton flavor violating decays of the neutral Higgses in an extended mirror fermion model with non-sterile electroweak-scale right-handed neutrinos and a horizontal A4 symmetry in the lepton sector. It is demonstrated that for the 125 GeV scalar h there is tension between the recent LHC result B(h→τμ)∼1% and the stringent limits on the rare processes μ→eγ and τ→(μ/e)γ as well as the muon anomalous magnetic dipole moment Δaμ from low energy experiments.